O-031 Comparison of techniques for stent-assisted coil embolization of aneurysms. (12th July 2011) - Spiotta, A; Wheeler, A; Smithason, S; Hui, F; Moskowitz, S
Abstract : Introduction: Stent assisted coiling (SAC) of aneurysms has been adopted with potential mechanical, hemodynamic and biologic properties imparting an advantage over coil embolization alone. Several strategies have emerged within the technique of SAC. The purpose of this investigation is to compare each of these techniques employed in SAC at a single institution with regards to clinical, technical and angiographic complications and success. Methods: We identified patients who underwent SAC between 2003 and 2010. Stenting technique is as follows: the first is "jailing" of the microcatheter in which a stent is deployed after the aneurysm is catheterized, but before coil deployment. The microcatheter is effectively pinned between the intima and outer confines of the stent and the coils are kept within the aneurysm and outside of the reconstructed vessel lumen. A second strategy is the "coil-through", in which a stent is first fully deployed across the aneurysm neck and then the aneurysm is catheterized by navigating through the tines of the stent. Third, the "coil-stent" technique involves an unassisted coil embolization to completion, immediately followed by stent deployment. Lastly, the "balloon-stent" method involves a stent placement after completion of a balloon-assisted embolization. Other potential techniques are utilized less frequently as demanded by the individual clinical situation. These alternate techniques included coiling with "Y-stent" configuration for basilar tip aneurysms and depositing single or multiple stents for flow diversion to treat blister dorsal carotid wall aneurysms. The inpatient and outpatient clinical charts, procedural reports, angiographic and non-invasive radiological images were analyzed to determine the anatomical and procedural details and adverse events. Immediate post- procedural angiograms as well as follow-up imaging were studied to assess the degree of aneurysm occlusion. Results: Two hundred and sixty aneurysms were identified. "Coil-through" technique was employed in 37.3%, "balloon-stent" in 36.2%, "jailing" in 10.8% and "coil-stent" technique in 7.7%. Overall rate of adverse events was higher with the "coil-stent" and "jailing" technique compared to the "balloon-stent" technique. The "coil-through" technique was associated with a significantly lower packing density (31.4±20%) than all other techniques ("coil-stent" 45.4±22%, "jailing" 42.2±20%, "balloon-stent" 44.3±22%). Among "coil-stent" patients, an initial Raymond 1 was achieved in 40%, compared to 57% of "jailing", 28% of "coil-through" and 63% of "balloon-stent" cases. The "coil-through" technique had a significantly lower rate of initial Raymond 1 remaining complete occluded on follow-up imaging compared to "balloon-stent" and "jailing". Conclusion: Balloon-assisted coil embolization followed by adjunctive stent deployment across the aneurysm neck appears to be the superior technique among stent-assisted coiling methods at our institution. It combines a lower rate of thrombotic and coil-related complications with a high rate of complete occlusion on initial and follow-up imaging.